Coming to Life: A Review of Movie Comics: Page to Screen/Screen to Page: Movie Comics: Page to Screen/Screen to Page, Blair Davis, Rutgers University Press, 295 pages, 2017, ISBN: 978-0-8135-7225-3. Issue 1 (15th March 2017) - Labarre, Nicolas
Abstract : This book review provides an overview of Movie Comics: Page to Screen/Screen to Page by Blair Davis (Rutgers University Press, 2017 ) a book which examines the reciprocal adaptations of film into comics and comics into films from 1930 to 1960. This review argues that Movie Comics provides a useful and finely-textured cultural history of that phenomenon, which help contextualize scholarly studies of contemporary adaptations and transmedia constructions.